2020
DOI: 10.4236/ojapps.2020.104011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Activated Milt Residence Time on Landlocked Fall Chinook Salmon Egg Survival

Abstract: During artificial spawning of salmonids, activated sperm is allowed to remain in contact with eggs for variable durations. This study examined multiple residence times (20, 40, 60, 90, or 120 seconds) for activated sperm on landlocked fall Chinook salmon (Oncorhynchus tshawytscha) eggs during spawning. There was no significant difference in egg survival to the eyed-stage of development or to hatch among any of the treatments, with a mean (SE) percent survival to the eyed stage of 63.9 (5.8). These results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The results of this study indicate that activated milt residence times for fall Chinook Salmon in Lake Oahe can be reduced to as low as 20 s without affecting egg survival, which is even less than the 30‐s residence time that was used successfully by Burrows (1949). These results also validate results from the small‐scale experiment reported by Shannon et al (2020). The lack of effect of such short milt residence times is not unexpected.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study indicate that activated milt residence times for fall Chinook Salmon in Lake Oahe can be reduced to as low as 20 s without affecting egg survival, which is even less than the 30‐s residence time that was used successfully by Burrows (1949). These results also validate results from the small‐scale experiment reported by Shannon et al (2020). The lack of effect of such short milt residence times is not unexpected.…”
Section: Discussionsupporting
confidence: 91%
“…One 50‐mL tube of milt was split between the two egg containers, followed by 1 L of lake water (8°C; total hardness as CaCO 3 = 220 mg/L; alkalinity as CaCO 3 = 160 mg/L; pH = 8.2; total dissolved solids = 440 mg/L) to initiate fertilization (Barnes and Cordes 1992). After the addition of lake water to the milt and eggs, two activated milt residence times were used (one for each container of eggs): 20 and 60 s. Longer milt duration times were not used because this experiment occurred during actual production spawning when time was at a premium and Shannon et al (2020) found no difference in egg survival between 60 and 120 s. At the end of each treatment, the eggs were immersed in lake water for approximately 10 s to rinse excess milt from them (Piper et al 1982). After rinsing, the eggs were placed in a 3.79‐L plastic bag containing approximately 1 L of lake water, placed in a cooler, and allowed to water harden for approximately 1 h (Hayes and Armstrong 1942).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations